Estudo sobre timo de ratos carentes em vitamina E - Silva, P. T. P.; Higuti, L. H.; Nascimento, A. J.; Hadler, W. A.; Cruz, A. O. (Acta Biológica Paranaense, 1984)
Estudo sobre timo de ratos carentes em vitamina E